Pesan Dakwah Melalui Akun Tiktok Dalam Melestarikan Nilai Islami Pada Gen Z - Aflachal Muthowah (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
Da'wah is very important to create a harmonious, peaceful, and of course in accordance with Islamic teachings. Da'wah messages and means are important components of the da'wah process. All materials derived from the Qur'an and Al-Hadith, which serve as the main source and guide of Islamic religious teachings, are included in the da'wah message. Young preachers among teenagers make innovations by preaching through the TikTok application and as a target is Generation Z by presenting interesting da'wah themes related to the problems faced by teenagers. There are several problems that can be formulated from the explanation of how the message of da'wah aqidah, morals, and shari'ah is. This study conducts descriptive research with a qualitative approach. The purpose of the descriptive qualitative approach is to describe the video content on the tiktok accounts of young preachers. With the characteristics and traits of generation z that are more open to differences and more accepting of diversity, making generation.